Robust lateral control of cars: Towards a reduction of pessimism and an easy trade-off between performance, comfort and robustness. Issue 5 (2019) - Mustaki, Simon; Chevrel, Philippe; Yagoubi, Mohamed; Fauvel, François; Kvieska, Pedro
Abstract: This paper presents a methodology to design a Lane Centering Assistance (LCA) system. It proposes an original approach to deal with the large parametric uncertainties encountered by automotive design engineers. Indeed, the same controller is supposed to be used for a specific vehicle regardless its configuration (tire, load, motorization, etc.). The methodology consists in a gradual insertion of the designers expertise in order to reduce as much as possible the inherent pessimism of a multi-model design approach. It also proposes some direct parameters to easily adjust the sought trade-off between performance (low lateral error) and driving feeling (jerks). The proposed design process is validated by high-fidelity simulations using complete nonlinear vehicle models.